In-vitro microleakage of repaired fissure sealants: a randomized, controlled trial - V. SRINIVASAN, & Z. NUGENT (Paediatric Dentistry, 2005)
The aim of this study was to investigate whether differences in surface treatment prior to repair influenced the seal of a resin fissure sealant placed on the occlusal surfaces of permanent molar teeth.